2007
DOI: 10.1016/j.biomaterials.2007.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Role of plasma fibronectin in the foreign body response to biomaterials

Abstract: Host responses to biomaterials control the biological performance of implanted medical devices. Upon implantation, synthetic materials adsorb biomolecules which trigger an inflammatory cascade comprising coagulation, leukocyte recruitment/adhesion, and foreign body reaction. The foreign body reaction and ensuing fibrous encapsulation severely limit the in vivo performance of numerous biomedical devices. While it is well established that plasma fibrinogen and secreted cytokines modulate leukocyte recruitment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
82
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 32 publications
2
82
0
1
Order By: Relevance
“…Again, experiments revealed that PMN-related responses are altered and bacterial coupling sites are masked or presented (3,4,12,34,38,43,44). In the presented study, plasma coating influenced the PMN-related receptor expression, which was mainly caused by a delamination of gelatine and primary effect of the material.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…Again, experiments revealed that PMN-related responses are altered and bacterial coupling sites are masked or presented (3,4,12,34,38,43,44). In the presented study, plasma coating influenced the PMN-related receptor expression, which was mainly caused by a delamination of gelatine and primary effect of the material.…”
mentioning
confidence: 63%
“…The augmented shedding in native polyester can be explained by an improved contact to the material due to fibrinogen. Several groups have elucidated the specific binding sites (21,43,44). Native polyester induced also greater magnitudes fort he mediators IL-8 and LTB 4 than gelatine-coated polyester did.…”
mentioning
confidence: 99%
“…The fibrous response to implanted materials involves binding of fibronectin to integrins on the cell surface. 20 In our previous work that examined integrin expression and function in skeletal cells, it was shown that both were disrupted in FGFR3 À/À MSC grown ex vivo 21 and contributed to a fibrous peri-implant response in FGFR3…”
Section: Discussionmentioning
confidence: 98%
“…interactions with plasma fibronectin that do not necessarily contribute to an optimal bone ingrowth. They may instead lead to negative effects like foreign body reaction and fibrotic processes (5,6). Specific tuning of the material surface can be used to minimize these non-specific effects and may rely on the molecular mechanisms of cell adhesion mainly mediated by integrins which provide selective interactions with the proteins of the extracellular matrix (7).…”
Section: Introductionmentioning
confidence: 99%